ANALISIS NILAI SOSIOLOGIS CERITA EMAS DI DOLOK PINAPAN DAERAH PULO GODANG, KEC. PAKKAT, KAB. HUMBANG HASUNDUTAN - Evi Melpa L. Gaol (JURNAL SASTRA INDONESIA (SASINDO), 2013)
Sociology and literature alike outlining the problem. Man'srelationship with his family, environment, customs-customs, andothers. Furthermore sociology as a science that tries to express thesocial problems again. Gold in Dolok Pinapan story is one formof oral literature Toba Batak community property, which isprecisely Pulogodang, Pakkat District, District HumbangHasundutan. This study aimed to describe the composition of thestories and events that happened in the legend Pulogodang,structured and translated into a story and explore the valuescontained therein sociology. This research is a qualitativedescriptive study, prioritize the meaning and context, the role ofresearcher of high demand. Informants in this study there were 6people in the two cultural experts Pulogodang, one king custom inPulogodang, three people Pulogodang.Temuan end of study wassociology there are three values that are relevant to today'ssociety, and one is no longer relevant sociological value BatakToba.Keywords: Sociology of Literature, Stories, and community